SOCIAL NETWORKING SITES ADDICTION DAN TANTANGANNYA BAGI PENDIDIKAN AGAMA ISLAM - Fahmi Riady (ADIBA : JOURNAL OF EDUCATION, 2026)
The rapid development of social networking sites (SNS) has significantly transformed social interaction patterns, ways of life, and identity formation. Numerous studies indicate that excessive SNS use may develop into a form of behavioral addiction, commonly referred to as social networking sites addiction, as comprehensively analyzed by Kuss and Griffiths through ten key lessons addressing its characteristics, mechanisms, and impacts. This article aims to examine the challenges posed by SNS addiction to Islamic Religious Education (Pendidikan Agama Islam/PAI) and to formulate relevant educational implications based on the findings of Kuss and Griffiths. This study employs a qualitative literature-based approach using conceptual and critical analysis of Kuss and Griffiths’ work, supported by relevant literature in Islamic education and behavioral psychology. The findings reveal that SNS addiction presents major challenges for PAI, including weakened self-regulation, distorted life orientation, identity crises, decreased learning concentration and religious engagement, shifts in social interaction patterns, and limitations in current pedagogical approaches of Islamic education in addressing digital addiction. Based on these challenges, the article emphasizes the need to reorient Islamic Religious Education toward strengthening self-regulation, integrating social media addiction issues into the curriculum, developing reflective and contemplative learning methodologies, and adopting an integrative educational approach that combines Islamic values with contemporary psychological insights. Consequently, Islamic Religious Education is expected to play a strategic role in shaping learners who are faithful, morally grounded, and responsible in navigating digital life.